Rotational atherectomy of right coronary artery complicated with stent dislodgment and ostial dissection – case report - Zimoch, Wojciech; Gaul, Georg; Wojtczak, Marcin; Kubler, Piotr; Reczuch, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Highly calcified lesions in coronary arteries are a frequent cause of percutaneous coronary intervention failure. In such cases rotational atherectomy seems to be an efficient alternative that allows facilitation of the calcified atherosclerotic plaque and ensures successful treatment. We present a case of rotational atherectomy of the right coronary artery complicated with stent dislodgment and ostial dissection.